Sufentanil intratecal para revascularização do miocárdio - Nigro Neto, Caetano (2014)
Context:Cardiac surgery patients undergoing coronary artery bypass grafting with cardiopulmonary bypass. Objective:Evaluate the effect of adding intrathecal sufentanil to general anesthesia on hemodynamics. Design:Prospective, randomized, not blinded study, after approval by local ethics in Research Committee. Setting:Monocentric study performed at Dante Pazzanese Institute of Cardiology, São Paulo, Brazil. Patients:40 consenting patients undergoing elective coronary artery bypass, both genders. Exclusion criteria:Chronic kidney disease; emergency procedures; reoperations; contraindication to spinal block; left ventricular ejection fraction less than 40%; body mass index above 32 kg/m2 and use of nitroglycerin. Interventions:Patients were randomly assigned to receive intrathecal sufentanil 1 μg/kg or not. Anesthesia induced and maintained with sevoflurane and continuous infusion of remifentanil.Main outcome measures:Hemodynamic variables, blood levels of cardiac troponin I, B-type natriuretic peptide, interleukin-6 and tumor necrosis factor alfa during and after surgery. Results:Patients in sufentanil group required less inotropic support with dopamine when compared to control group (9.5% vs 58%, p = 0.001) and less increases in remifentanil doses (62% vs 100%, p = 0.004). Hemodynamic data at eight different time points and biochemical data showed no differences between groups. Conclusions:Patients receiving intrathecal sufentanil have more hemodynamical stability, as suggested by the reduced inotropic support and fewer adjustments in intravenous opioid doses.